TEACHER WORK IN HIGHER EDUCATION: HISTORICAL BACKGROUND AND CURRENT FEATURES - Maria das Graças Martins da Silva (Editora da Universidade de Santa Cruz do Sul, 2009)
The text examines the trajectory of the teacher work in higher education and highlights the current signs of changes in the production of that work. In the investigative way, it presents a historical overview of higher education in Brazil and of the teacher work and also reviews part of the literature that discusses the topic today. It concludes that the educational policies, historically speaking, acted as change inducers and that teaching currently, presents unique alterations that tend to reflect on the teaching and on the educational aims. Key words: teacher work; higher education; educational policies; teacher's background.